Integrating cultural perspectives in online ablution water usage monitoring: a design for sustainability - Ghazali, Ihwan; Tanjung, Tia; Irianto, Irianto; Muhida, Riza; Herawan, Safarudin Gazali; Asih, Hayati Mukti (Frontiers in Communication, 2024)
Water is an important resource for performing ablution before prayer. However, lack of communication and information between prayer congregations regarding the amount of water used during ablution, the absence of environmental protection consciousness, and the impact of cultural behavior can be the factors causing wasteful water use during ablution. This study aims to design and implement an internet-based monitoring system that integrates cultural values in evaluating ablution water consumption. The correlation between cultural dimensions and preferences for an online monitoring system of ablution practices was examined using confirmatory factor analysis and structural equation modeling. The results showed that uncertainty avoidance, power distance, and long-term orientation were identified to significantly influence online monitoring preferences for ablution activities. The preferences of sensor accuracy, safety case to cover from water, and durable material were determined as the most important design specifications for online monitoring systems. The real-time evaluation of online monitoring was performed through smartphone applications and web-based interfaces. Considering cultural preferences when developing a water monitoring system strategy can increase awareness regarding environmental sustainability, advocate for conscientious water management, and control water usage. The inclusion of cultural value in the design process is expected to provide valuable insights for product designers when establishing design specifications. Additionally, it expands the usefulness of Hofstede's cultural theory in the context of the creation and development of products.